1988
DOI: 10.1161/01.res.62.5.1019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of CO2 response in cerebral arteries of the newborn pig: role of phospholipase, cyclooxygenase, and lipoxygenase pathways.

Abstract: The role of phospholipase, lipoxygenase, and cyclooxygenase pathways in the mechanism of the cerebrovascular response to CO2 and H+ was investigated in newborn piglets. Responsiveness of pial arterioles, 48-206 micron diameter, to inhalation of 6% CO2 and to suffusion of acidic cerebrospinal fluid (CSF, pH = 6.84), adenosine (10(-4) M), or theophylline (10(-2) M) was studied using a closed cranial window. Pial arteriolar diameter was measured using intravital microscopy. Phospholipase inhibitors quinacrine hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 38 publications
2
52
0
Order By: Relevance
“…The magnitude of the relaxation was very similar to that which we observed previously in phenylephrine preconstricted aortic rings (Sweeney et al 1998a) and is in agreement with the widely reported relaxant effect of acidosis in systemic vessels (Tobian et al 1959;Kontos et al 1977a,b;Wagerle & Mishra, 1988;Nielsen et al 1991;Austin & Wray, 1993;Fukuda et al 1993;Wagerle & Degiulio, 1994;Tian et al 1995;Peng et al 1998). In isohydric hypercapnia, however, the tension in PGF2á preconstricted carotid arteries was unchanged.…”
Section: Resultssupporting
confidence: 90%
“…The magnitude of the relaxation was very similar to that which we observed previously in phenylephrine preconstricted aortic rings (Sweeney et al 1998a) and is in agreement with the widely reported relaxant effect of acidosis in systemic vessels (Tobian et al 1959;Kontos et al 1977a,b;Wagerle & Mishra, 1988;Nielsen et al 1991;Austin & Wray, 1993;Fukuda et al 1993;Wagerle & Degiulio, 1994;Tian et al 1995;Peng et al 1998). In isohydric hypercapnia, however, the tension in PGF2á preconstricted carotid arteries was unchanged.…”
Section: Resultssupporting
confidence: 90%
“…The direct action of C 0 2 and various other mediators, such as perivascular pH and bicarbonate ion, on the cerebral vessel wall remains controversial, and prostanoids have been recently implicated (33). Indomethacin, a prostaglandin synthetase inhibitor, has been found to abolish this response in preterm infants (34), as well as in rats (35) and gerbils (36), although not in some other experimental animals (37).…”
Section: Materlals and Methodsmentioning
confidence: 99%
“…Thus, if one assumes that adenosine plays no role in mediating cerebral hypercapnic hyperemia, and vasoactive prostanoids produced secondary to CO2-induced increases in hydrogen ion concentra tions are the predominant mediators (Wagerle and Mishra, 1988;Leffler et al, 1989), then our results indicate that adenosine does not interfere with the prostanoid-based vasodilative mechanism, a possi bility raised by previous studies (Ally et al, 1977). Second, our data suggest that the attenuated or abolished CO2 reactivity occurring during hypoten sion (Harper and Glass, 1965;Wei et al, 1980) and hypoxia (McPherson et al , 1987) occurs indepen dently of the many physiologic actions of adeno sine, since concentrations of this nucleoside are el evated under these conditions (Park et al , 1987Van Wylen et al , 1988).…”
Section: Discussionmentioning
confidence: 99%
“…A hypercap nia-induced increase in extracellular hydrogen ion concentration is likely to be the initial step of this process (Kontos et aI., 1977), but hydrogen ion may not be the final effector. There is evidence that the hyperemia in newborn animals results from hydro gen ion-stimulated production of vasodilative pros tanoids (Wagerle and Mishra, 1988;Leffler et aI., 1989). The purine metabolite adenosine has also been hypothesized to participate in the mediation of hypercapnic vasodilation, based on studies in which adenosine receptor blockade reduced hypercapnia-stimuli was inversely proportional to vessel size.…”
mentioning
confidence: 99%